2008
DOI: 10.1063/1.3013437
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric properties of core-shell particulate nanocomposites

Abstract: In this study, we report results on magnetoelectric (ME) core-shell Pb(Zr,Ti)O3 (PZT)-NiFe2O4 (NF) particulate nanocomposites. NF particles forming the shell had size in range of 20–30 nm. The grain size of sintered nanocomposites was found to be in the range of 500–800 nm. The sintered nanocomposite exhibited piezoelectric coefficient (d33) of 60 pC/N, dielectric constant of 865, and ME coefficient of 195 mV/cm Oe. High ME coefficient was observed for wide range of dc bias magnetic field. This approach of fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tatarenko et al [131] reported the converse ME effect over the [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] GHz range in bilayers of single crystal ZnY and polycrystalline PZT or single crystal PMN-PT. The resonator was tuned by 120 MHz with E = 12 kV/cm, and corresponding ME coupling strength A was about 10 MHz cm/kOe.…”
Section: Resonatorsmentioning
confidence: 99%
“…Core/shell (ferrite/piezoceramic) structured composites have been synthesized to avoid the contact of the conductive ferrite particles during sintering [17]. Unlike the other cases, Islam et al [18] reported a PZT core/NiFe 2 O 4 shell ME composite (Figure 3c). To circumvent the problem of high conductivity through the ferrite phase, a 100-mm layer of PZT was used to cover both faces of the sintered pellet.…”
Section: Bulk Me Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…These magnetoelectric responses are induced by stress mediation between the two phases according to the principles of product properties [4,5], and therefore depend on the intrinsic properties of each phase and on the mechanical coupling between them. Materials with a high piezoelectric constant such as Pb(Zr, Ti)O 3 and BaTiO 3 are selected as the ferroelectric phase, whereas Terfenol-D, FeBSiC and ferrites with high magnetostrictive parameters are chosen as the magnetic phase [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It is easier to tailor the magnetoelectric properties in a composite than in the individual phases by adjusting the volume fractions and interactions among the components.…”
Section: Introductionmentioning
confidence: 99%
“…Several ways have been proposed, such as using functionally graded materials [15][16][17], choosing curved structures-annular bilayer structures [18] or cylindrical layered composites [19][20][21][22], introducing nanocomposites [23][24][25][26], taking advantage of material nonlinearity [27,28], among others.…”
Section: Introductionmentioning
confidence: 99%